PELATIHAN HIDROPONIK DI YAYASAN ASOFA AKSELERASI SODAQOH FIQRUL AKBAR, KAB. BEKASI - Annisa Nur Ichniarsyah; Heny Agustin; Maulidian Maulidian (STMIK Royal, 2019)
Abstract: urban farming means to cultivate and nurture animals in a city or within its rural area. There are variety of plants that could be grown namely vegetables and fruits. Urban agriculture is expeted to help improve the economy of the people in an area because the yields produced can provide economic benefits. The Asofa Foundation tried to capture this opportunity in the context of developing a masjid-based economy through hydroponic training for the surrounding community. Therefore, a series of training was conducted to improve the capacity of the community. The training included training on seeding vegetables in rockwool, training on transplanting, and training in preparing and mixing hydroponic fertilizers. The results of the training were that residents were able to cultivate plants using hydroponics. However, the boundary was the environmental conditions (in this case water) in Bekasi which were not good enough so that the seedlings died after being transplanted into the hydroponic kit. Further training needed can be in the form of training fruit plants using hydroponics which can withstand inadequate water conditions. Another training that can be carried out is training in vegetable cultivation with planting methods other than hydroponics that are able to accommodate environmental conditions Keywords: urban farming, economic development, masjid-based economy, trainings Abstrak: Pertanian perkotaan adalah menanam dan memelihara binatang ternak di dalam atau sekitar kota. Beragam jenis tanaman dapat dibudidayakan terutama tanaman sayuran dan buah. Pertanian perkotaan mampu membantu peningkatan ekonomi rakyat di suatu daerah karena hasil panen yang dihasilkan dapat memberikan keuntungan ekonomis. Peluang inilah yang berusaha ditangkap oleh Yayasan Asofa dalam rangka pengembangan ekonomi berbasis masjid lewat pelatihan hidroponik untuk masyarakat sekitar. Oleh karena itu, dilakukanlah serangkaian pelatihan untuk meningkatkan kemampuan masyarakatnya. Pelatihan yang dilakukan antara lain pelatihan penyemaian tanaman sayuran di rockwool, pelatihan pindah tanam, dan pelatihan meracik pupuk hidroponik. Hasil dari pelatihan tersebut adalah warga mampu melakukan budidaya tanaman dengan menggunakan hidroponik hanya saja kondisi lingkungan (dalam hal ini air) di daerah Bekasi kurang baik sehingga tanaman semaian mati setelah dipindahkan ke dalam kit hidroponik. Pelatihan lanjutan yang diperlukan dapat berupa pelatihan tanaman buah dengan menggunakan hidroponik yang tahan kondisi air yang kurang memadai. Pelatihan lain yang dapat dilakukan adalah pelatihan budidaya tanaman sayuran dengan metode tanam selain hidroponik yang mampu mengakomodasi kondisi lingkungan. Kata kunci: pertanian perkotaan, pengembangan ekonomi, ekonomi berbasis masjid, pelatihan